CXCR4 inhibitor AMD3100 disrupts the interaction of multiple myeloma cells with the bone marrow microenvironment and enhances their sensitivity to therapy - Azab, Abdel Kareem; Runnels, Judith M.; Pitsillides, Costas; Moreau, Anne Sophie; Azab, Feda; Leleu, Xavier; Jia, Xiaoying; Wright, Renee D.; Ospina, Beatriz; Carlson, Alicia L.; Alt, Clemens; Burwick, Nicholas R.; et al. (My University, 2009)
The interaction of multiple myeloma (MM) cells with their microenvironment in the bone marrow (BM) provides a protective environment and resistance to therapeutic agents. We hypothesized that disruption of the interaction of MM cells with their BM milieu would lead to their sensitization to therapeutic agents such as bortezomib, melphalan, doxorubicin, and dexamethasone. We report that the CXCR4 inhibitor AMD3100 induces disruption of the interaction of MM cells with the BM reflected by mobilization of MM cells into the circulation in vivo, with kinetics that differed from that of hematopoietic stem cells. AMD3100 enhanced sensitivity of MM cell to multiple therapeutic agents in vitro by disrupting adhesion of MM cells to bone marrow stromal cells (BMSCs). Moreover, AMD3100 increased mobilization of MM cells to the circulation in vivo, increased the ratio of apoptotic circulating MM cells, and enhanced the tumor reduction induced by bortezomib. Mechanistically, AMD3100 significantly inhibited Akt phosphorylation and enhanced poly(ADP-ribose) polymerase (PARP) cleavage as a result of bortezomib, in the presence of BMSCs in coculture. These experiments provide a proof of concept for the use of agents that disrupt interaction with the microenvironment for enhancement of efficacy of cytotoxic agents in cancer therapy
Keywords: Multiple myeloma; Bone marrow; Animal experimentation; Apoptosis; Cells; Mice